Loyola and Lutheranism: Counter Reformist or Reformist? - García Mateo, SJ, Rogelio (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
From the Schism of the West and the Council of Constanza (1414), throughout the 15th-century and into the 16th-century diverse movements of Reform in the Church develop. Some of them crystallize in the Protestant Reformation. Leaving aside stereotypes often attributed to the Society of Jesus as a form of anti-Lutheran militancy, Ignatius of Loyola should be considered today as a beacon of reform within the Catholic Church. This article goes a step further, studying more in depth the relation between Ignatius and his first companions amidst waves of reform and how they influenced the thought and identity of the first Society along with the attitudes that accompanied these Jesuits in their dialogue with reformers.
Keywords: Reform; Church; Jesuits; Society of Jesus; religious dialogue; ecumenism